The First Flight of the SPIDER Balloon-Borne Telescope - Rahlin, Alexandra Sasha (Princeton, NJ : Princeton University, 2016)
The CMB is an imprint of the initial conditions that were laid down early in the history of the Universe and evolved into the large scale structure that exists today. The inflationary paradigm provides an elegant mechanism for creating the observed homogeneous, isotropic and flat Universe, with structure sourced by adiabatic and nearly Gaussian perturbations. The paradigm testably predicts a divergence-free polarization component in the CMB, whose amplitude is directly related to the energy scales that drove inflation. CMB observations have reached sensitivities required to constrain the simplest models of inflation via this so-called B-mode signal. This dissertation covers the first flight of the SPIDER instrument, from hardware integration through launch and preliminary analysis of results. SPIDER is a balloon-borne polarimeter designed to characterize the polarization of the CMB and intervening foregrounds at microwave frequencies on degree angular scales. For the inaugural flight from McMurdo Station, Antarctica in January 2015, we deployed over 2000 detectors distributed across three telescope receivers at each of 150 GHz and 94 GHz. A follow-up flight is scheduled for 2017-2018, adding 280 GHz receivers optimized for constraining Galactic dust. Key contributions include (1) electrical and thermal integration of the receivers with the cryogenic system, pointing system and readout electronics; (2) optimization of the radiative environment of the detectors; (3) design and implementation of automated receiver control software; (4) architecture of the data processing and mapmaking pipeline; (5) preliminary maps and angular spectra progressing toward a state-of-the-art wide-field measurement of the B-mode signal.